Impacts of girls' education empowerment programme on the economic well-being of Katsina Rural Society, Nigeria - Abdullahi, Ibrahim (2014)
Girls Education Empowerment Programme (GEEP) was introduced in 2007 in Rural Katsina to empower poor girl through education in order to increase the economic wellbeing of her family. The wellbeing of low income group among rural family is a great concern and had initiates this study. This study aimed to identify the backgrounds of GEEP stakeholders (the respondents), their empowerment, and the wellbeing level, as well as to measure the impact of GEEP on their economic wellbeing. The significant indicators through empowerment elements (independent variables) in determining the economic wellbeing (dependent variable) of the stakeholders of GEEP were also measured. The Empowerment Theory by Nikkah, (2010), Economic Wellbeing Model by Joo (1999) and Laily et al. (2009) underlined the research framework for this study. A structured questionnaire was specially developed and used in this study. There were three parts in the questionnaire – the empowerment and economic wellbeing scale as well as the question on respondents’ background. In this study, educational empowerment was measured through empowerment scales consisting of cognitive, resource control, social capital, and awareness. On the other hand, the economic wellbeing was measured through four elements - life satisfaction, infrastructural assets, economic hardship and family perception. The population of this study was derived from three selected Local Government Area (LGAs) and comprised of 542,428 GEEP stakeholders. A total of 400 respondents were selected as a sample in this study. After screening of completed questionnaires, the return rate was 88.75%. Administration of the questionnaire as well as data collection was carried out by trained male and female enumerators. The general and household backgrounds of the respondents were captured in the descriptive analyses, as well as levels of empowerment and economic wellbeing; and the impact of GEEP after five years on the economic wellbeing of the respondent. Additionally, list of indicator variables were analyzed in correlation with the economic wellbeing. All analyses were conducted by gender disaggregated data in order to capture any gender differences. This study obtained a mean monthly income of USD306 for male and USD96 for female respondents; and at 28.7% of males and 12.1% of females are employed. The male respondents constituted of 35% and females at 18% with tertiary background of education. There were male respondents at 11.3% and female at 40% were in a low income group. The finding shows significant association (p<0.05), between mean score in the overall level of empowerment groups with sex of the respondents. The majority (58.6%) of respondents were in the moderate level of empowerment. However, only cognitive and resource control elements, shows a significant association (p<0.05) between the male and the female respondents. Furthermore the correlation between empowerment elements and economic wellbeing elements show moderate correlation (r=0.3-0.4). On the other hand, in Male Research Model (MRM), the correlation between empowerment and economic wellbeing shows low correlation (r=0.2), and indeed the MRM was not significantly fit the data. Finally the cognitive variable had found to have most significant (p<0.005) contribution (β=0.189) for the General Research Model (GRM) and (β=0.258) Female Research Model (FRM) on the economic wellbeing. In MRM the resource control was found to be the only significant (p<0.05) variable (β=0.251), but the MRM was not fit the data in this study. In conclusion data from this study revealed a significant association between empowerment and economic wellbeing of female and male respondents in Katsina state, Nigeria. Additionally a significant difference in economic wellbeing of the respondent was also captured after five years of GEEP. Data from this study will be useful in assessment and implementation of empowerment policies especially in rural community settings, particularly in Nigeria. Indeed the findings can assist the development of current GEEP programme for future use.